2006
DOI: 10.1016/j.neuroimage.2006.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the human left fusiform gyrus to sublexical orthographic structure

Abstract: Neuropsychological and neurophysiological evidence point to a role for the left fusiform gyrus in visual word recognition, but the specific nature of this role remains a topic of debate. The aim of this study was to measure the sensitivity of this region to sublexical orthographic structure. We measured blood oxygenation (BOLD) changes in the brain with functional magnetic resonance imaging while fluent readers of English viewed meaningless letter strings. The stimuli varied systematically in their approximati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
212
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(249 citation statements)
references
References 68 publications
(83 reference statements)
25
212
0
1
Order By: Relevance
“…For example, degrading stimulus quality increases RT more in older adults than younger adults, whereas the effects of varying word frequency remain relatively consistent in aging (Madden 1988;Allen et al 1995). In addition, at the functional neuroanatomic level, extrastriate regions showing greater activation in the young group have been associated with orthographic processes (Petersen et al 1990;Cohen et al 2003;Binder et al 2003Binder et al , 2006. In contrast, inferior temporal regions showing greater activation in the older group have typically been associated with semantic knowledge (Nobre et al 1994;Martin et al 1995;Martin and Chao 2001;Sharp et al 2004), and the mid-LIPC region (ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, degrading stimulus quality increases RT more in older adults than younger adults, whereas the effects of varying word frequency remain relatively consistent in aging (Madden 1988;Allen et al 1995). In addition, at the functional neuroanatomic level, extrastriate regions showing greater activation in the young group have been associated with orthographic processes (Petersen et al 1990;Cohen et al 2003;Binder et al 2003Binder et al , 2006. In contrast, inferior temporal regions showing greater activation in the older group have typically been associated with semantic knowledge (Nobre et al 1994;Martin et al 1995;Martin and Chao 2001;Sharp et al 2004), and the mid-LIPC region (ca.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that different regions within this network play different roles in LD. Extrastriate regions have been linked with orthographic processes such as visual feature extraction and mapping visual patterns onto lexical representations (Petersen et al 1990;Binder et al 2003Binder et al , 2006Cohen et al 2003;Gold et al 2006). In contrast, inferior temporal regions have most typically been associated with semantic processes (Nobre et al 1994;Martin et al 1995;Martin and Chao 2001;Sharp et al 2004), and left inferior frontal regions have been shown to contribute to multiple high-level linguistic processes (Petersen et al 1988;Demb et al 1995;Thompson-Schill et al 1997;Badre et al 2005;Gold et al 2005, Gold et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…7 We shall not comment on the purely visual aspects of word recognition or on visual-to-lexical transcoding (Perfetti, 1999). Here we only assume that structures in the inferior temporal lobe can act as interfaces between the visual system and the lexicon (Binder et al, 2003;Binder, Medler, Westbury, Liebenthal, & Buchanan, 2006;Cohen et al, 2000;Devlin, Jamison, Gonnerman, & Matthews, 2006;Nobre, Allison, & McCarthy, 1994), perhaps in cooperation with other brain areas (Mechelli, Gorno-Tempini, & Price, 2003;Price & Devlin, 2003). The mapping from visual input to lexical structures stored in the Memory component is represented by arrow 1 in Figure 3.…”
Section: Towards a Dynamic Account Of The N400 1355mentioning
confidence: 99%
“…One set of studies showed that its sensitivity to visual words is independent of changes in case, font, size, and location (Dehaene et al, 2001(Dehaene et al, , 2004Polk & Farah, 2002) but is dependent on orthographic regularity and GPC rules (Bentin et al, 1999;Fiebach, Friederici, Muller, & von Cramon, 2002;Hsu et al, 2009). Based on such evidence, several researchers suggested that N170's specialization was orthography (Binder, Medler, Westbury, Liebenthal, & Buchanan, 2006;Vinckier et al, 2007).…”
Section: Visual Word Recognition: Also Expertise For Character Likeness?mentioning
confidence: 99%